Global photosynthetic capacity is optimized to the environment. (4th January 2019) - Smith, Nicholas G.; Keenan, Trevor F.; Colin Prentice, I.; Wang, Han; Wright, Ian J.; Niinemets, Ülo; Crous, Kristine Y.; Domingues, Tomas F.; Guerrieri, Rossella; Yoko Ishida, F.; Kattge, Jens; Kruger, Eric L.; et al.
Abstract: Earth system models (ESMs) use photosynthetic capacity, indexed by the maximum Rubisco carboxylation rate ( V cmax ), to simulate carbon assimilation and typically rely on empirical estimates, including an assumed dependence on leaf nitrogen determined from soil fertility. In contrast, new theory, based on biochemical coordination and co‐optimization of carboxylation and water costs for photosynthesis, suggests that optimal V cmax can be predicted from climate alone, irrespective of soil fertility. Here, we develop this theory and find it captures 64% of observed variability in a global, field‐measured V cmax dataset for C3 plants. Soil fertility indices explained substantially less variation (32%). These results indicate that environmentally regulated biophysical constraints and light availability are the first‐order drivers of global photosynthetic capacity. Through acclimation and adaptation, plants efficiently utilize resources at the leaf level, thus maximizing potential resource use for growth and reproduction. Our theory offers a robust strategy for dynamically predicting photosynthetic capacity in ESMs.